Red cell distribution width (RDW) and neutrophil-to-lymphocyte ratio (NLR) as predictors of outcome in acute pancreatitis - Saha, Dipanwita; Sutradhar, Probir Kumar; Alam, Md Shafiul; Islam, Fahmida; Saha, Anita; Fatema, Kaniz; Hassan, Md Shariful; Karim, ASM Bazlul (Journal of Bangladesh College of Physicians and Surgeons, 2024)
BACKGROUND Acute pancreatitis is a commonly encountered emergency in children. It has always been tough to predict accurately among the patients who will become systemically unwell. Simple prognostic markers, such as red cell distribution width (RDW) and neutrophil-to-lymphocyte ratio (NLR), could identify such patients. This study was done to assess the usefulness of those markers. METHODS This cross-sectional study was conducted from July 2018 to June 2020 at department of Pediatric Gastroenterology and Nutrition, BSMMU, Dhaka. Thirty-one children with abdominal pain diagnosed as acute pancreatitis were included by purposive sampling in the study. RESULTS The mean age of the pediatric patients was 11.19 (±3.45) years. The mean red cell distribution width was 14.99 (±2.96) and mean neutrophil-to-lymphocyte ratio was 4.49 (±3.99). Total thirty patients (97%) were recovered and one patient (3%) died in hospital stay. Thirteen patients (41.9%) developed complications among which ascites was more common (12, 38.7%). NLR> 5 was observed in higher proportion in the study subjects with complications (46.2%) than without complications (16.7%) without any statistically significant difference. RDW ≥14 was found in 53.8% study subjects with complications and 50% without complications. However, no statistically significant difference was found. Length of hospital stay was longer in patients with NLR >5 than with NLR ≤5. RDW <14 was associated with longer hospital stay than RDW ≥14. There was no statistically significant difference. CONCLUSION It was found that elevated RDW and NLR on admission had unfavorable clinical outcomes for pediatric patients with acute pancreatitis although statistical significance could not be established. Further multicenter studies with larger sample size are required for making some clinically applicable inference. J Bangladesh Coll Phys Surg 2024; 42: 259-264